A taxonomic revision of Tillandsia (Tillandsioideae, Bromeliaceae) from Uruguay - Rossado, Andrés J.; Donadío, Sabina; Bonifacino, José M. (Phytotaxa, 2024)
A taxonomic revision of the genus Tillandsia (Bromeliaceae) from Uruguay is here presented based on the examination of herbarium specimens, field surveys, and an extensive analysis of taxonomic literature. Nineteen taxa are recognized: 17 species, one subspecies, and one natural hybrid. A new identification key for all the species of Tillandsia occurring in the country is presented. Data on nomenclature (correct names, types, synonyms used in Uruguay) are provided for each taxon, along with detailed morphological descriptions, vernacular names, distribution and habitat information (global and local), phenology, conservation assessment, diagnostic characters, and nomenclatural and taxonomical notes. This information is complemented with images, illustrations of floral parts, maps showing species distribution in Uruguay, and a phenological diagram. Tillandsia arequitae and T. uruguayensis are endemic to Uruguay, and five species reach their southern limit of distribution in the country (T. bandensis, T. geminiflora, T. ixioides, T. loliacea, and T. stricta). Tillandsia capillaris and T. virescens are registered as exotic and subspontaneous. A new natural hybrid between T. aëranthos and T. recurvifolia is described. Three species previously cited for Uruguay (T. crocata, T. lorentziana, and T. streptocarpa) are excluded or cited as doubtful species for the country. Tillandsia bicolor is discarded as a synonym of T. aëranthos, and T. dianthoidea is considered for the first time as an illegitimate superfluous name. Lectotypes for Tillandsia arequitae (second-step), T. capillaris, T. circinalis (second-step), T. cordobensis (second-step), T. duratii, T. geminiflora (second-step), T. hieronymi (second-step), T. ixioides, T. microxiphion, T. recurvata, T. stricta (second-step), T. tricholepis (second-step) and T. virescens, as well as an epitype for T. aëranthos are designated.